Bone morphogenetic protein 4 regulates microRNA expression in breast cancer cell lines in diverse fashion. Issue 3 (18th December 2015) - Alarmo, Emma‐Leena; Havunen, Riikka; Häyrynen, Sergei; Penkki, Sanna; Ketolainen, Johanna; Nykter, Matti; Kallioniemi, Anne
Abstract : Bone morphogenetic protein 4 (BMP4) is a remarkably powerful inhibitor of breast cancer cell proliferation, but it is also able to induce breast cancer cell migration in certain cellular contexts. Previous data demonstrate that BMP4 controls the transcription of a variety of protein‐coding genes, but not much is known about microRNAs (miRNA) regulated by BMP4. To address this question, miRNA expression profiles following BMP4 treatment were determined in one mammary epithelial and seven breast cancer cell lines using microarrays. While the analysis revealed an extensive variation in differentially expressed miRNA across cell lines, four miRNAs (miR‐16‐5p, miR‐106b‐5p, miR‐23a‐3p, and miR‐23b‐3p) were commonly induced in a subset of breast cancer cells upon BMP4 treatment. Inhibition of their expression demonstrated an increase in BT‐474 cell number, indicating that they possess tumor suppressive properties. However, with the exception of miR‐106b‐5p, these effects were independent of BMP4 treatment. Scratch assay with miR‐16‐5p and miR‐106b‐5p inhibitors on BMP4‐treated MDA‐MB‐231 cells resulted in enhanced cell migration, suggesting that these miRNAs are engaged in BMP4‐induced motility. Taken together, we have for the first time characterized the BMP4‐induced miRNA expression profiles in breast cancer cell lines, showing that induced miRNAs contribute to the fine‐tuning of proliferation and migration phenotypes. © 2015 Wiley Periodicals, Inc.